A DSL-based Approach to Product Derivation for Software Product Line - Nesrine Lahiani; Djamal Bennouar (Acta Informatica Pragensia, 2016)
Product derivation is an important part of the Software Product Line (SPL) development process. The quality of a product derivation process has a direct impact in decreasing software product costs and time-to-market. In this paper, we present an approach that represents the SPL with a set of integrated models and automatically derives executable products with model transformations. We combine SPL and Model-Driven Engineering (MDE) into a comprehensive and extremely effective framework in order to get advantages of both techniques. In order to evaluate the feasibility of our approach, we have designed and implemented it using existing and available technologies.